The Efficacy and Development of Students' Problem-Solving Strategies During Compulsory Schooling: Logfile Analyses - Molnár, Gyöngyvér; Csapó, Benő (Frontiers in Psychology, 2018)
The purpose of this study was to examine the role of students’ exploration strategies used in the first phase of problem solving. The sample for the study was drawn from 3rd- to 12th-grade students (aged 9–18) from Hungarian schools (n=4371). Problems designed in the MicroDYN approach with different levels of complexity were administered to the students via the eDia online platform. Logfile analyses were performed to unveil the impact of strategy use on the efficiency of problem solving. Students’ exploration behaviour was coded and clustered by Latent Class Analyses. Several theoretically effective strategies were identified, including the vary-one-thing-at-a-time (VOTAT) strategy and its sub-strategies. The results of the analyses indicate that the use of a theoretically effective strategy, which extract all information required to solve the problem, did not always lead to high performance. Conscious VOTAT strategy users proved to be the best problem solvers followed by the non-conscious VOTAT strategy users and the non-VOTAT strategy users. In the primary school sub-sample, six qualitatively different strategy class profiles were distinguished. The results shed new light on and provide a new interpretation of previous analyses of the processes of complex problem solving. They also highlight the importance of explicit enhancement of problem-solving skills and problem-solving strategies as a tool for knowledge acquisition in new contexts during and beyond school lessons.